The effect of cash on delivery (COD) payments on purchasing decisions of the Wamena Community: A case study of Shopee - Fitri, Fitri; Syarifah, Syarifah; Thomas, Rianik (Universitas Islam Indonesia, 2024)
IntroductionIndonesians, especially when shopping online, increasingly use the cash on delivery (COD) system to pay for goods.ObjectivesThis study aims to determine the effect of the cash on delivery (COD) payment method on the purchasing decisions of the Wamena community on the Shopee e-commerce platform.MethodThis research method uses an approach. The type of research used, namely the mixed method, is a research method that combines quantitative and qualitative data to produce more comprehensive data. The sample used amounted to 100 respondents who actively use Shopee in Wamena. Quantitative research measures the Cash on Delivery (COD) variable through Convenience, Privacy, and Trust. The purchasing decision variable is measured through indicators of Problem recognition, Information search, and Evaluation of alternatives. The data analysis techniques used in this study are validity tests, reliability tests, correlation tests, regression tests, t-tests, and determination coefficient tests.ResultsThe results showed that the COD payment method positively and significantly affected the purchasing decisions of the Wamena city community at Shopee E-Commerce. The contribution given by the cod variable is 49% to purchasing decisions. Researchers conducted interviews to strengthen the results. The interview results show that the people of Wamena city choose cod payment because the average estimated delivery from Java to Papua is at least 7 days, so buyers find it easier to control expenses because they only pay when the goods are in hand. This payment system is also felt to be able to avoid bills that come after transactions and can control excessive shopping desires.ImplicationsWith the increasing trend of COD usage, this study's results underscore the importance of buyers' and sellers' protection for this type of transaction.Originality/Novelty This study contributes to studies on online purchasing, especially in areas outside Java Island, where facilities and infrastructure are limited to support fast delivery.